SOSIALISASI PENCEGAHAN TINDAK PIDANA DI LINGKUNGAN REMAJA MELALUI EDUKASI HUKUM - Gunawan Widjaja (Lafadz Jaya Publisher, 2026)
This article discusses the promotion of crime prevention amongst young people through legal education as a preventative measure aimed at fostering a legally aware younger generation. Adolescents are a vulnerable age group, susceptible to environmental influences, peer pressure and the development of digital technology, all of which can trigger deviant behaviour and criminal acts. This paper employs a literature review method, examining various relevant sources, such as books, journals and scientific documents relating to legal education and the prevention of juvenile delinquency. The findings indicate that legal education plays a crucial role in enhancing adolescents’ knowledge, awareness and law-abiding attitudes. Effective socialisation strategies need to involve families, schools, the community and law enforcement agencies through interactive, participatory and sustainable approaches. Thus, legal education can serve as a strategic means of preventing criminal offences amongst adolescents and fostering a young generation characterised by responsibility and integrity.